Book Reviews - Tate, Roger D.; Pennington, Loren E.; Gentry, Robert J.; Pease, Arthur S.; Spidle, Jake W.; Shea, William L.; Tate, Michael L.; Sellen, Robert W.; Coate, Charles; Nickell, Frank; et al. (Teaching History: A Journal of Methods, 1983)
H. Wayne Morgan. Drugs in America: A Social History, 1800-1980. Syracuse, New York: Syracuse University Press, 1981. Pp. xi, 233. Cloth, 20.00. Review by Roger D. Tate of Somerset Community College. Michael T. Isenberg. War on Film: The American Cinema and World War I, 1914-1941. Rutherford, New Jersey: Fairleigh Dickinson University Press, 1981. Pp. 273. Cloth, 27.50. Review by Loren E. Pennington of Emporia State University. Bertell Ollman and Edward Vernoff, eds. The Left Academy: Marxist Scholarship on American Campuses. New York: McGraw-Hill Book Co., 1982. Pp. vii, 290. Paper, 8.95. Review by Robert J. Gentry of The University of Southwestern Louisiana. James West Davidson and Mark Hamilton Lytle, eds. After the Fact: The Art of Historical Detection. New York: Alfred A. Knopf, 1982. Vol. I: Pp. xxxii, 204. Paper, 6.95. Vol. II: Pp. xxxii, 220. Paper, 6.95. Review by Arthur S. Pease of Lebanon School District, Lebanon, N.H. David Birmingham. Central Africa to 1870: Zambezia, Zaire and the South Atlantic. New York: Cambridge University Press, 1981. Pp. vii, 177. Paper, 9.95. Review by Jake W. Spidle of the University of New Mexico. James Kirby Martin and Mark Edward Lender. A Respectable Army: The Military Origins of the Republic, 1763-1789. Arlington Heights, Illinois: Harlan Davidson, Inc., 1982. Pp. xvi, 240. Paper, 7.95. Review by William L. Shea of the University of Arkansas at Monticello. Bruce A. Rosenberg. The Code of the West. Bloomington: Indiana University Press, 1982. Pp. vi, 213. Cloth, 15.00. Review by Michael L. Tate of the University of Nebraska at Omaha. Ralph B. Levering. The Cold War, 1945-1972. Arlington Heights, Illinois: Harlan Davidson, Inc., 1982. Pp. xi, 165. Paper, 6.95. Review by Robert W. Sellen of Georgia State University. Fay D. Metcalf and Matthew T. Downey. Using Local History in the Classroom. Nashville: American Association for State and Local History, 1982. Pp. x, 284. Cloth, 17.50. Review by Charles Coate of Eastern Oregon State College. William Graebner and Leonard Richards, eds. The American Record: Images of the Nation’s Past. New York: Alfred A. Knopf, 1982. Vol. I, Pp. 421. Paper, 9.95. Vol. II, Pp. 449. Paper, 9.95. Review by Frank Nickell of Southeast Missouri State University. Thomas Ladenburg and Christopher Bairstow. Who Killed JFK: Need We Know? Brookline, Massachusetts: Brookline-Cambridge Dissemination Center, 1978. Pp. 31. Paper, 1.10. Review by James F. Marran of New Trier Township High School, Winnetka/ Northfield, Illinois. Thomas Ladenburg. America in Indochina. Brookline, Massachusetts: Brookline-Cambridge Dissemination Center, 1977. Pp. 50. Paper, 1.40. Review by Richard A. Diem of The University of Texas at San Antonio. Thomas J. Schlereth. Artifacts and the American Past. Nashville, Tennessee: American Association for State and Local History, 1980. Pp. vii, 294. Cloth, 13.95. Review by Michael B. Husband of Palisade, Colorado.